PERLINDUNGAN ANAK DALAM KELUARGA MENURUT AL QUR’AN - Siti Fatimah; Selly Virgo Riska (AZZAHRA, 2020)
This research was motivated by the concern of Al-Qur'an for children, which is the greatest gift from Allah s.w.t. Children as the greatest gift should be properly cared for. In this case the family has an important role, because it is the first place of refuge for a child. One of the verses in the al-Qur'an which instructs to provide protection for children, namely Q.S. al-Tahrim [66]: 6. However, ironically, nowadays violence against children is rampant. What is more concerning is that some of the perpetrators of these acts of violence are the closest people to the child; relatives and even parents. Even though parents or relatives should be the first and foremost people in protecting children, because a child still cannot protect himself. The objectives of this study are: 1) To explain the function of the family in an Islamic perspective. 2) To explain the essence of children in the Qur'an. 3) To explain the forms of child protection in the family according to the Qur'an. The research method used is library research (library research), with the object of research on the al-Qur'an book and supported by several other books. By using the method of tafsir maudhu'i (thematic). The results showed that: 1) The family in the view of Islam plays a very important function, namely: religious function, biological function, reproductive function, economic function, psychological function, educational function, and social function. 2) Children as a gift from Allah s.w.t. in the Koran it has two connotations, namely positive and negative connotations. 3) The forms of child protection in the family according to the Qur'an, namely: first, protection of children before birth, protection of children after birth, and protection of children in special conditions.